1996
DOI: 10.1021/ic9606901
|View full text |Cite
|
Sign up to set email alerts
|

Magnetochemical Properties and Reactions of Vanadium(III) Thiolate Complexes:  Preparation of (NEt4)3[V3Cl6(edt)3] and Mixed-Valence (NEt4)[V2(edt)4] (edt = Ethane-1,2-dithiolate)

Abstract: Reactions of the previously reported dinuclear vanadium(III) thiolate anion [V(2)(edt)(4)](2)(-) (edtH(2) = ethane-1,2-dithiol) are described. Treatment of (NEt(4))(2)[V(2)(edt)(4)] (1) in MeCN with equimolar (C(12)H(8)S(2))BF(4) (C(12)H(8)S(2)(+) = the thianthrenium radical cation) results in a one-electron oxidation and isolation of the V(III),V(IV) complex (NEt(4))[V(2)(edt)(4)] (2). The same product can also be obtained by controlled-potential electrolysis of 1 at -0.20 V vs Ag/AgCl. Treatment of 1 in CH(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…The fit also deviated from paramagnetic behavior below 150 K and gave a θ value of –7.69 K, suggesting a weak antiferromagnetic interaction, likely between neighboring clusters. Similar weak antiferromagnetic coupling has also been reported in other vanadium complexes and clusters 29. Considering that the cluster has an odd number of total valence electrons, the one unpaired electron resides alone on the highest occupied molecular orbital (HOMO).…”
Section: Resultssupporting
confidence: 78%
“…The fit also deviated from paramagnetic behavior below 150 K and gave a θ value of –7.69 K, suggesting a weak antiferromagnetic interaction, likely between neighboring clusters. Similar weak antiferromagnetic coupling has also been reported in other vanadium complexes and clusters 29. Considering that the cluster has an odd number of total valence electrons, the one unpaired electron resides alone on the highest occupied molecular orbital (HOMO).…”
Section: Resultssupporting
confidence: 78%
“…7-11 The V-S distances in 1a and 2a are similar to the corresponding V-S(bridged) distances in [V 3 Cl 6 (edt) 3 ] 3-(edt = ethane-1,2-dithiolate; average 2.408(11) Å), which is a rare example containing the V III S 6 chromophore. 18 Complex 2a has somewhat longer V-S bonds than 1a. This seems to be caused by stronger affinity of iridium toward sulfur atoms than that of rhodium.…”
Section: X-ray Crystal Structuresmentioning
confidence: 96%
“…Redox properties, via CV, indicated that [V 2 (edt) 4 ] 2− undergoes two oxidation processes to V(IV) and V(V) ( Table 9, entry 1b), while the V(IV) species, formed with one S atom, [VS(edt) 2 ] 2− , displays no reversible redox processes, a result already reported by the same authors [195], with only an irreversible oxidation process at E pa = −0.46 V vs NHE was observed. The same compound, [V 2 (edt) 4 ] 2− , was studied again few years later (Table 9, entry 1c [196]). …”
Section: Electrochemistry Of Vanadium(iii) Compoundsmentioning
confidence: 99%